(3CYjGf GdYUQ hCYhGf GdfUQs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdGeGe GdYGde GdaGUd GdYdGeI ChMO GdaUMGA JGL GdGOHGA s
(3BNQgG (B:s
(3jQhi Yf CHj HcQ GdWhWhSi hJhai QMeg Gddg JYGdi ai Pi GdMLI SfI CQHYI YTQ hSHYeGjI hbO RGO Ydi GdKeGfjf GTgQG s
(3GdfSNI eUhQI Yf fSNI YGTQ CafOi HGdBSJGfIs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
Keywords: (3GdJGQjNs